2005
DOI: 10.1111/j.1600-079x.2005.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization and interactions of melatonin in dry cholesterol/lecithin mixed reversed micelles used as cell membrane models

Abstract: The state of melatonin confined in dry cholesterol/lecithin mixed reversed micelles dispersed in CCl4 was investigated using 1H-NMR and FT-IR spectroscopies as a function of the melatonin to lecithin molar ratio (R(MLT)) and of the cholesterol to lecithin molar ratio (R(CHL)). An analysis of experimental results leads to the hypothesis that, independent of R(MLT) and as a consequence of anisotropic melatonin/lecithin, melatonin/cholesterol and cholesterol/lecithin interactions, melatonin is totally solubilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 29 publications
3
56
1
Order By: Relevance
“…Figure 1 shows the IR spectrum of a b-CD-containing resin synthesized using the method above. It has a large negative peak corresponding to the OH stretching at the 3391 cm )1 position that was reported by Bongiorno et al [23] for pure b-CD crystals. This indicates that the resin contains a large amount of OH groups contributed by b-CD.…”
Section: Resultsmentioning
confidence: 68%
“…Figure 1 shows the IR spectrum of a b-CD-containing resin synthesized using the method above. It has a large negative peak corresponding to the OH stretching at the 3391 cm )1 position that was reported by Bongiorno et al [23] for pure b-CD crystals. This indicates that the resin contains a large amount of OH groups contributed by b-CD.…”
Section: Resultsmentioning
confidence: 68%
“…Similar results have been also achieved by analysis of MLT containing anhydrous micellar systems. 33 These data can justify also the strong protection effect, almost against free radicals, of MLT on cell membranes, that have been reported. [4][5][6][7][8] Infrared spectra on the solid complex demonstrated that in the formation of inclusion complexes an important contribution is due to polar bonds formation-modification, thus evidencing once more 33 that MLT is preferentially localised in interfacial nano-districts, between polar and apolar domains.…”
Section: Discussionmentioning
confidence: 67%
“…These interactions can also alter the physicochemical properties and thus the functioning of the membranes. Melatonin is one of the most important molecule among the endogenous molecules that could change membrane properties, because it penetrates all physiologic barriers [11,38,39]. Moreover, melatonin and its metabolites have antioxidant properties that prevent damage induced by reactive species through several mechanisms, principally as a scavenger of these oxidative agents [40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%